Religious Parenting Transmitting Faith and Values in Contemporary America - Smith, Christian 1960- (Princeton University Press, 2019)
How parents approach the task of passing on religious faith and practice to their childrenHow do American parents pass their religion on to their children? At a time of overall decline of traditional religion and an increased interest in personal "spirituality," Religious Parenting investigates the ways that parents transmit religious beliefs, values, and practices to their kids. We know that parents are the most important influence on their children’s religious lives, yet parents have been virtually ignored in previous work on religious socialization.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 22. Okt 2019)
Keywords: SOCIAL SCIENCE / Sociology of Religion; Intergenerational communication -- Religious aspects; Intergenerational relations -- Religious aspects; Parental influences -- United States; Parenting -- Religious aspects; Religion and sociology -- United States